2009
DOI: 10.1080/00288330909509995
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution ofArtemiaand mussel as food for cultured middle‐stagePanulirus japonicusphyllosomata as determined by stable nitrogen isotope analysis

Abstract: ± 0.4‰. Calculations based on these measurements indicated that 66% of all nitrogen in the bodies of the phyllosomata were derived from Artemia and 34% from mussel gonad, suggesting that Artemia is the more important food item for phyllosomata with a body length of c. 10 mm and at least 99 days of age. Our results indicate that the analysis of stable nitrogen isotope ratios is a useful diagnostic tool to estimate the relative assimilation rates of different food items.Abstract Artemia and mussel gonad represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(46 reference statements)
0
12
0
2
Order By: Relevance
“…Stage 1 phyllosoma have been shown to readily consume newly hatched Artemia nauplii and are seemingly able to draw sufficient nutrition to fuel the requirements of basal metabolism and moulting through to subsequent developmental stages. However, the long-term viability of phyllosoma as they progress through later developmental stages is greatly compromised when fed a diet of Artemia alone, an outcome directly attributable to the less than optimal nutritional profiles of commercially available Artemia species, which generally deliver a poor source of essential long-chain fatty acids (Matsuda et al 2009). Ultimately, in consideration that phyllosoma likely have a limited ability to desaturate and elongate shorter-chained omega-3 fatty acids, the provision of preformed n-3 LC-PUFA is necessitated despite an abundance of 18:3n-3 in Artemia nauplii.…”
Section: Artemia Sp As Live Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage 1 phyllosoma have been shown to readily consume newly hatched Artemia nauplii and are seemingly able to draw sufficient nutrition to fuel the requirements of basal metabolism and moulting through to subsequent developmental stages. However, the long-term viability of phyllosoma as they progress through later developmental stages is greatly compromised when fed a diet of Artemia alone, an outcome directly attributable to the less than optimal nutritional profiles of commercially available Artemia species, which generally deliver a poor source of essential long-chain fatty acids (Matsuda et al 2009). Ultimately, in consideration that phyllosoma likely have a limited ability to desaturate and elongate shorter-chained omega-3 fatty acids, the provision of preformed n-3 LC-PUFA is necessitated despite an abundance of 18:3n-3 in Artemia nauplii.…”
Section: Artemia Sp As Live Feedmentioning
confidence: 99%
“…Therefore, lipid loading/enrichment of Artemia is a common practice in marine hatcheries. Generally, Artemia are subjected to a~24-h enrichment period posthatch, thus providing a biologically encapsulated means of providing fortified nutrition to developing larvae (Liddy et al 2003;Ritar et al 2003;Nelson et al 2004;Matsuda et al 2009). As such, numerous commercial preparations are now readily available for Artemia enrichment, effectively permitting the tailoring of fortified phyllosoma nutrition across a host of desirable bioactive nutrients.…”
Section: Artemia Sp As Live Feedmentioning
confidence: 99%
“…Mass-balance mixing models can be applied to estimate dietary contributions under the assumption that the isotopic composition of a consuming organism equals the weighted average of the isotopic composition of its diet constituents (Martı´nez del Rio & Wolf 2005). The use of mixing models has been of special assistance to conduct dietary reconstructions in animals living in marine and littoral environments (Riera & Richard 1996, Dang et al 2009, Granek et al 2009), and to develop experimental studies aimed at quantifying nutrient incorporation in farmed marine species (Schroeder 1983, Burford et al 2004, Gamboa-Delgado & Le Vay 2009b, Matsuda et al 2009). The use of preanalyzed dietary components with contrasting isotopic values allows distinguishing and quantifying the contribution of resources after they have been allocated physiologically (Fischer et al 2004, Gamboa-Delgado & Le Vay 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…This feeding behaviour makes it diffi cult to investigate how much of Artemia and mussel gonad they consume and assimilate. Matsuda et al (2009) tried to estimate the relative assimilation of the two diets by cultured larvae of P. japonicus by using stable nitrogen isotope analysis. Calculations based on the measurements of the ratios of 15 N to 14 N in the bodies of phyllosoma (mean BL = 9.3 mm), Artemia and mussel gonad indicated that 66% of all nitrogen was derived from Artemia and 34% from mussel gonad, suggesting that Artemia is the more important food item at this larval size.…”
Section: Larval F Oods -L Ive I Nert and F Ormulated O Ptionsmentioning
confidence: 99%